Examining the efforts of government Internal Supervisory Apparatus (APIP) in enhancing bureaucratic reform, organizational integrity, and risk management: An efficiency analysis - Kurniawan Permana; Chindy Chresna Agung Bujana (Integritas: Jurnal Antikorupsi, 2024)
The efficiency level of APIPs should be a concern for the government to ensure that the allocated resources are optimally used to fulfill their role in preventing and detecting corruption. This study investigates the efficiency level of APIP using Data Envelopment Analysis (DEA). The number of employees and spending budget ratios of APIP are used as input, and ministries and regional government’s bureaucratic reform, risk management, and integrity perception score as output. Those outputs are selected since they represent the indicators of an effective anti-corruption effort. Applying a purposive sampling of 50 APIPs at the ministerial and regional levels, this study shows that only seven APIPs (14%) achieve maximum efficiency level. Furthermore, this study develops an algorithm to set those APIPs as a reference group by other similar APIPs based on the characteristics of inputs and output. Lastly, this study employs quadrant analysis to map the APIP’s efficiency level and its capabilities. It finds that 14 APIPs are relatively efficient and capable, while 35 APIPs are capable but not relatively efficient, and one APIP is not capable or efficient. This study could be used to design a more detailed and tailor-made agenda for strengthening APIP as an essential element in combating corruption in Indonesia.